Evaluation of the Palatal Features in Relation to Graft Harvesting in the Saudi Population - Razan Alaqeely; Sumaiah Ajlan; Faisal Alsanqar; Abdulmahsin Alaqil; Abdulaziz Almansour; Mohammad A. Aldosari (Medicina)
Background and Objectives: The palate’s morphological characteristics are of great importance, especially in periodontology, where the palatine tissue represents a source of tissue graft for multiple mucogingival surgeries. This study aimed to estimate the amount of donor tissue available through the average palatal height and average location of the greater palatine artery in the Saudi population according to age and gender. Materials and Methods: Digital casts for adult Saudi patients at the age of 18–60 years old with a mean age of 37.76 ± 12.68 years were collected and analyzed using EXOCAD software. The digital casts were evaluated, and measurements of arch width at molars and canines, palatal vault height (PVH), palatal height index (PHI), and extension of the palatal rugae were registered. Finally, the amount available for soft tissue graft harvesting was calculated. Results: Overall, 109 maxillary casts for Saudi patients, 52 (47.7%) males and 57 (52.3%) females, were analyzed. The maxillary inter-molar arch width, inter-canine width, and palatal vault height significantly differed between males and females (p < 0.05). The mean PHI was 45.51% ± 8.12%, and 27.5% were classified as orthostaphyline, while 72.5% were categorized as hypsistaphyline, with no significant difference between the genders. The mean maximum graft width was 11.45 mm, and the graft width was significantly different between males and females (p < 0.005), while the mean maximum graft length was 17.78 mm, and the graft length showed no significant difference. Conclusions: The results of this study provide specific clinical guidelines for periodontal procedures by emphasizing the importance of gender-specific anatomical considerations. Data on graft dimensions and palatal measurements will enable the exact planning of soft tissue harvesting to minimize surgical risks and optimize mucogingival surgery outcomes in the Saudi population.